Testing the cosmological Poisson equation in a model-independent way - Zheng, Ziyang; Sakr, Ziad; Amendola, Luca (Physics letters, 2024)
We show how one can test the cosmological Poisson equation by requiring only the validity of three main assumptions: the energy-momentum conservation equations of matter, the equivalence principle, and the cosmological principle. We first point out that one can only measure the combination M≡Ωm(0)μ, where μ quantifies the deviation of the Poisson equation from the standard one and Ωm(0) is the fraction of matter density at present. Then we employ a recent model-independent forecast for the growth rate f(z) and the expansion rate E(z) to obtain constraints on M for a survey that approximates a combination of the Dark Energy Spectroscopic Instrument (DESI) and Euclid. We conclude that a constant M can be measured with a relative error σM=4.5%, while if M is arbitrarily varying in redshift, it can be measured only to within 13.4% (1 σ c.l.) at redshift z=0.9, and 15-22% up to z=1.5. We also project our constraints on some parametrizations of M proposed in literature, while still maintaining model-independence for the background expansion, the power spectrum shape, and the non-linear corrections. Generally speaking, as expected, we find much weaker model-independent constraints than found so far for such models. This means that the cosmological Poisson equation remains quite open to various alternative gravity and dark energy models.